Institutional entrepreneurship in building the Brazilian market of functional yogurts. Issue 1 (6th January 2014) - Almeida, Felipe; de Paula, Nilson; Pessali, Huascar
Abstract : Purpose: – The aim of this paper is to present an analytical narrative of the construction of the Brazilian market of functional yogurt, highlighting the role of Danone as an institutional entrepreneur. Design/methodology/approach: – After putting together a theoretical basis from business studies and institutional economics, the paper explores factual evidence of strategic moves by dairy firms in Brazil. Findings: – Danone, despite being a second mover, has been able to effectively make use of new values and collective concerns regarding food functionality to create a favourable institutional set in which to operate. Other firms have not been able to challenge its position in the market, simply abiding by the concepts and values created by Danone. Practical implications: – On the one hand, case studies based on traditional economic theories usually approach markets with supply and demand adjustment tools or taking technology as exogenous and the sole determinant of the existence of a market. On the other hand, traditional business theories highlight an individual entrepreneur as the only relevant object of analysis. This study offers an alternative guideline to study markets with creative players that craft not only new physical products or directly delivered services, but also concepts and ideas. Studies of other markets or similar markets in different countries can benefit from its insights. Originality/value: – The functional yogurt market in Brazil has not previously been object of academic research, and the combined framework of analysis in this study may offer guidance for other market studies.